Analisis Daya Kecambah dan Viabilitas Benih Kacang Hijau (Vigna Radiata L.) - Irpan Noerdin; Karrisa Zahratul Shaumi; Lindiyani Lindiyani; M Renald Kevin Setia Hadi (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
This research aims to analyze mung bean seed viability through germination observations under two different treatments. Observations were conducted over 15 days, measuring parameters including germination rate, normal seed count, abnormal seed count, and seed mortality rate. Results showed significant differences between treatments, with treatment 1 achieving 72% germination rate while treatment 2 reached 64%.